Assessment of Passengers’ Satisfaction of Public Transport System in Akure-Owo Axis, Nigeria - Samuel Oluwaseyi, Olorunfemi; Adetayo Olaniyi, Adeniran (American International Journal of Multidisciplinary Scientific Research, 2018)
This study assesses passengers’ satisfaction of public transport system in Akure-Owo axis, Nigeria. It was necessitated by the poor nature of transport system which has created impediments to the smooth movement of people, goods and services in some of urban centres in Nigeria. Meanwhile, the importance of public transport in cities of many developing countries lies in the fundamental fact that accessibility and mobility are essential for economic growth and also for effective and efficient movement of goods and services. Twelve bus services were identified. The study was conducted using questionnaires and field observation to collect the required data at the terminals (i.e. Akure and Owo Park). One hundred and twelve (112) questionnaires were administered to the passengers across the two terminals. Descriptive tool such as weighted mean and standard deviation were employed. Also, Gap analysis was used to achieve descriptive statistics. Findings revealed that passengers were not satisfied with the competence of drivers, condition of vehicle, overloading and over-speeding, attitude of drivers, driver’s compliance with road safety rules and order, and the cost charge per trip. Based on the dissatisfactions, recommendations were suggested.